A student-implemented elective to improve medical student confidence in providing diabetes self-management support - Fazel MT (Advances in Medical Education and Practice, 2016)
Maryam T Fazel,1,2 Mohammad Fazel,3 Nora L Bedrossian,3 Fernando Picazo,3 Merri L Pendergrass1,4 1Department of Pharmacy Practice and Science, University of Arizona College of Pharmacy, 2Department of Medicine, University of Arizona College of Medicine -Tucson, 3University of Arizona College of Medicine-Tucson, 4Department of Medicine-Division of Endocrinology, University of Arizona College of Medicine-Tucson, Arizona, USA Background: The purpose of this study was to develop a preclerkship elective and assess its effectiveness in supplementing medical students’ education. Methods: A group of medical students under the guidance of two faculty advisors developed an elective consisting of six sessions covering a variety of practical aspects of diabetes care/education taught by an interprofessional team. Following the course completion, a survey was emailed to the enrollees who attended at least one session. The results were analyzed using Wilcoxon signed-rank and descriptive analyses. Results: A total of 14 medical students were enrolled (nine first year and five second year). An average of 4.4 sessions/student was attended. Thirteen students attended at least one session and were surveyed. The survey response rate was ~62% (8/13). All eight students indicated that the course was valuable and would recommend it to their colleagues. A Wilcoxon signed-rank test revealed a statistically significant increase in students’ confidence in all five areas assessed following participation in the course, P<0.05 with a large effect (r>0.5). Conclusion: This study suggests the feasibility of developing disease state-specific preclerkship elective courses and that such courses can be beneficial in supplementing medical student education with practical knowledge. Keywords: medical student, supplemental education, interprofessional education, diabetes self-management